The Optional Protocol to the International Covenant on Economic, Social and Cultural Rights: A Commentary - Julieta Rossi (Pretoria University Law Press (PULP), 2016)
On 10 December 2008, coinciding with the 60th anniversary of the Universal Declaration of Human Rights, the United Nations General Assembly adopted the Optional Protocol to the International Covenant on Economic, Social and Cultural Rights (OP-ICESCR). The Optional Protocol permits individuals or groups of individuals to submit complaints to the UN Committee on Economic, Social and Cultural Rights if they have exhausted domestic remedies and believe a ratifying State has violated their rights under the Covenant. It therefore effected an historic change in the UN human rights system in that it recognizes the equal status of claimants of economic, social and cultural rights and their right to access justice. The Protocol came into force on 5 May 2013, and the number of ratifications is steadily growing. This Commentary, the first and most comprehensive of its kind, offers rigorous scholarly commentary on the provisions of the OP-ICESCR, aimed at informing and encouraging research, reasoned argument, consistent interpretation and effective advocacy, adjudication and remedies under the Protocol. It provides a critical resource for both users of the Optional Protocol (applicants, lawyers, governments, the Committee) and a broader audience of scholars, students, national judiciaries and policy makers. The book is divided into three main sections that respectively address procedural issues, substantive interpretation, and remedies and enforcement. Each of the chapters highlights and discusses what is most innovative about the OP-ICESCR, as well as potential ambiguities and controversies. The Commentary makes a unique and critical contribution to legal scholarship and practice by laying the foundations for cutting-edge, authoritative jurisprudence. The chapters have benefited from a peer-review process, and an exchange and discussion among the authors and other experts.